Effect of ethanol and acetaldehyde at clinically relevant concentrations on atrial inward rectifier potassium current IK1: separate and combined effect - Horakova, Z; Matejovic, P; Pasek, M; Hosek, J; Simurdova, M; Simurda, J; Bebarova, M (Journal of physiology and pharmacology, 2016)
Atrial fibrillation is the most common arrhythmia at alcohol consumption. Its pathogenesis is complex, at least partly related to changes of cardiac inward rectifier potassium currents including IK1. Both ethanol and acetaldehyde have been demonstrated to considerably modify IK1 in rat ventricular myocytes. However, analogical data on the atrial IK1 are lacking. The present study aimed to analyse IK1 changes induced by ethanol and acetyldehyde in atrial myocytes. The experiments were performed by the whole cell patch-clamp technique at 23 ± 1°C on enzymatically isolated rat and guinea-pig atrial myocytes as well as on expressed human Kir2.3 channels. Ethanol (8 - 80 mM) caused a dual effect on the atrial IK1 showing the steady-state activation in some cells but inhibition in others in agreement with the ventricular data; on average, the activation was observed (at 20 mM by 4.3 and 4.5% in rat and guinea-pig atrial myocytes, respectively). The effect slightly increased with depolarization above -60 mV. In contrast, the current through human Kir2.3 channels (prevailing atrial IK1 subunit) was inhibited in all measured cells. Unlike ethanol, acetaldehyde (3 μM) markedly inhibited the rat atrial IK1 (by 15.1%) in a voltage-independent manner, comparably to the rat ventricular IK1. The concurrent application of ethanol (20 mM) and acetaldehyde (3 μM) resulted in the steady-state IK1 activation by 2.1% on average. We conclude that ethanol and even more acetaldehyde affected IK1 at clinically relevant concentrations if applied separately. Their combined effect did not significantly differ from the effect of ethanol alone.
Keywords: Drug Interactions; kultivované buňky; Potassium Channels, Inwardly Rectifying; Rats; ethanol; Guinea Pigs; Ethanol; Rats, Wistar; mužské pohlaví; draslíkové kanály dovnitř usměrňující; CHO Cells; Myocytes, Cardiac; krysa rodu Rattus; acetaldehyd; morčata; CHO buňky; Cells, Cultured; Acetaldehyde; zvířata; Humans; Cricetulus; lékové interakce; kardiomyocyty; potkani Wistar; lidé; Male; Animals